Neuroprotective effects of ethanol extraction from Rubia yunnanensis Diels on chronic cerebral hypoperfusion: modulation of the System Xc-/GSH/GPX4 axis to alleviate oxidative stress and ferroptosis - Cheng, Jianghao; Ma, Xiaoxia; Tao, Jie; Jiang, Xiaoli; Chen, Pu; Duan, Xiaohua (Frontiers in Pharmacology, 2025)
IntroductionVascular dementia (VD) is a neurodegenerative disease caused by chronic cerebral hypoperfusion (CCH), which considerably impact patients’ quality of life. Ethanol extraction from Rubia yunnanensis (RY-A) has gained attention for its potential neuroprotective effects, but its effects and mechanisms of action on CCH are unknown.MethodsAfter 30 days of RY-A gavage treatment in a CCH rat model, its effects were evaluated using the Morris water maze test, cerebral blood flow measurements, and HE staining of the brain. These findings, combined with serum medicinal chemistry, RNA-seq, and metabolomics analyses, revealed the active compounds and mechanisms of RY-A in CCH rats. The results were further validated using assay kits and Western blot techniques.ResultsRY-A treatment significantly attenuated neurological damage and improved cognitive function in CCH rats. Ultra-high-performance liquid chromatography high-resolution mass spectrometry identified 511 blood-entry compounds of RY-A. RNA-seq and metabolomic analysis showed that RY-A might help to normalize changes in gene and metabolite expression caused by CCH. RY-A induced neuroprotective effects by increasing the production of key proteins involved in ferroptosis inhibition, such as SLC7A11, SLC3A2, GSS, and GPX4, while increasing antioxidant enzyme activities and alleviating oxidative stress.ConclusionRY-A inhibited oxidative stress and ferroptosis by activating the System Xc-/GSH/GPX4 pathway and balancing iron metabolism, thereby attenuating CCH-induced neurological damage and cognitive deficits.